Post Covid-19 Doctor-Patient Relationship Model. Creation of Social Connection Contexts With Physical Distancing - Jose Luis Turabian (International Journal of General Practice, 2020)
The coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) 1 has produced a significant change in the way general medicine is conducted. This shift has been remarkably quick towards telecare. The form of the clinical interview has changed, and with it communication and the doctor-patient relationship; Before COVID-19, all communication techniques and doctor-patient relationship, which were considered tried and true to establish a good relationship with patients, involved physical proximity 2. Now in many European countries and in the United States face-to-face consultations have been reduced to 10-20%, with most contacts now being provided remotely using symptom checkers, electronic messaging, and phone or video consultations 3.
Keywords: COVID-19